2021
DOI: 10.1016/j.rbmo.2021.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the early phase of the COVID-19 pandemic on natural and ART-mediated birth rates in Lombardy Region, Northern Italy

Abstract: Declaration: Giovanni Corrao received research support from the European Community (EC), the Italian Agency of Drugs (AIFA) and the Italian Ministry for University and Research (MIUR). He has taken part in a variety of projects funded by pharmaceutical companies (i.e. Novartis, GSK, Roche, AMGEN and BMS). He has also received honoraria as a member of the advisory board to Roche. Edgardo Somigliana has received personal honoraria to give talks at international meetings from Theramex and Merck-Serono, received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…The ART clinics resumed their services in April 2020, which may have led to a compensatory increase in ART-conceived births and in multiple pregnancies. Our results are consistent with a prior study 35 that also showed an 86.6% drop in ART-conceived births in December 2020 in the Lombardy region in Italy.…”
Section: Discussionsupporting
confidence: 93%
“…The ART clinics resumed their services in April 2020, which may have led to a compensatory increase in ART-conceived births and in multiple pregnancies. Our results are consistent with a prior study 35 that also showed an 86.6% drop in ART-conceived births in December 2020 in the Lombardy region in Italy.…”
Section: Discussionsupporting
confidence: 93%
“…They suggested that such findings should be viewed in the context of stress-related outcomes triggered by this pandemic. [ 25 ] We noted similar live birth rates in ART cycles compared to those conducted in the pre-COVID times.…”
Section: Discussionsupporting
confidence: 57%
“…The significant impact on cumulative live birth rates due to the delay in fertility treatment was specifically significant in older women (>40 years old) ( Smith et al , 2020 ). In contrast, a study in Italy reported a decrease of 5.1% in the monthly birth rate in 2020 as compared to 2019, but calculated that this could be largely attributed to a decrease in natural conceptions while the closing of ART centres only played a marginal role ( Somigliana et al , 2021 ). Others have suggested that the pandemic may increase the importance of family and increase family building ( Lambalk et al , 2020 ).…”
Section: Introductionmentioning
confidence: 96%